Parenting Patterns In The Incidence Of Stunting In Children Under Five In Indonesia - Siti Shofiyah; Ruliati Ruliati; Imam Fatoni (CV. Inara, 2024)
The parenting provided by parents plays an important role in the growth and development of toddlers. Poor parenting can increase the incidence of stunting in toddlers. This research is qualitative with a literature study approach. Primary data sources were accessed from scientific journals, scientific books, videos, images and other sources that are compatible with this paper. The sources were sorted, analysed and conclusions were drawn.Parenting patterns are associated with the incidence of stunting in toddlers. These parenting patterns include exclusive breastfeeding, MP breastfeeding and immunisation completeness. It is recommended for parents to continue to provide exclusive breastfeeding until the baby is 6 months old. age of 6 months, provide complementary foods that contain balanced nutrition, and actively bring toddlers to the posy. balanced, and actively bring toddlers to the posyandu to get complete basic immunisations and monitor the nutritional status of toddlers so that and monitoring the nutritional status of toddlers so that it is expected that toddlers can grow and develop well.